Comparison of Bacterial and Dye Microleakage of Different Root-End Filling Materials - Kazem, Majid; Eghbal, Mohammad Jafar; Asgary, Saeed (Iranian Endodontic Journal, 2010)
INTRODUCTION: The provision of an effective apical seal is an essential factor when choosing an appropriate material for success of root-end surgeries. Root-end resection, preparation and obturation should provide an adequate apical seal. The aim of this in vitro study was to investigate bacterial and dye microleakage of four different root-end filling materials and compare the efficacy of these two methods. MATERIALS AND METHODS: Fifty-six single-rooted teeth with intact and straight roots were randomly assigned into four study groups of 12 each and two control groups of three each. After decoronation, root canals were prepared up to file size #40 using step back technique; then, they were filled with gutta-percha and AH26 sealer. Root-ends were resected 3 mm above the root-end and 3 mm deep cavities were prepared. Root-end cavities were filled with amalgam, Root Mineral Trioxide Aggregate (Root MTA), White ProRoot MTA (WMTA), and calcium enriched mixture (CEM) cement. Bacterial leakage was investigated in Trypticase Soy Broth (containing Enterococcus faecalis) after 70 days and 1% methylene blue dye leakage was assessed after 72 hours. Complete dye leakage was checked using stereomicroscope (×40). Data were statistically analyzed using Fisher Exact test. For pair comparison between the two methods Kapa agreement was utilized. RESULTS: After 70 days there was 100% bacterial leakage in amalgam, and CEM cement, 91.7% in WMTA, and 75% in Root MTA. This difference was not significantly different. The difference in complete dye leakage was also not significant (WMTA and CEM cement 16.7%, Amalgam and Root MTA 33.3%). CONCLUSION: There was no significant measure of agreement between dye and bacterial penetration along root-end fillings. CEM cement was not significantly different from currently used retrofilling materials e.g. WMTA.